Settling the Valley, proclaiming the Gospel: the general epistles of the Mormon First Presidency - Neilson, Reid Larkin; Waite, Nathan N. (Oxford University Press, 2017)
"Spanning the first decade after the Mormon exodus to the Salt Lake Valley, these fourteen "general epistles" were written by Brigham Young and his counselors in the church's First Presidency. They provide a glimpse of the Mormons' earliest years in the Great Basin and their simultaneous missionary efforts worldwide."--Provided by the publisher